(Dis)Affect, Photography, Place - Prieto-Blanco, Patricia (Imaginations)

(untitled) (York University, 2022)
Migrants are connected for a variety of reasons (Leurs and Prabhakar 2018, p. 247), and in a myriad of ways (Cabalquinto 2018; Özdemir, Mutluer, and Özyürek 2019; Gencel Bek and Prieto-Blanco 2020). Drawing from a larger project of ethnographic nature (Prieto-Blanco 2016b), this paper argues that photographic practices advance socialization in transnational families, and that each practice activates certain relational affordances to support bonding and familial intimacy. This also serves to offer an alternative reading of phatic communication (Malinowski 1923) as an emotion‐based process. Finally, the paper proposes to understand (digital) photography as a medium of (inter)action and experience for transnational families.